Determination Of Yersinia Spp. And Salmonella Paratyphi B Isolated From Possibly Contaminated Cream Samples In The City Of Tehran - Mohammad Mehdi Soltan Dallal; Hamid Emadi Koochak; Mohammad Kazem Sharifi Yazdi; Ali Taheri Mirghaed; Hamid Choobineh (Tehran University of Medical Sciences, 2014)
Background and Aim: Cream is a rich dairy product with the pH close to neutral and limited preservation capability. Cream is suitable and rich for microbial growth. In the past few decades, there was a great concern in contamination of food products. Salmonella and Yersinia species are two important pathogens causing food poisoning and human gastroenteritis. The aim of the present study is to investigate the quality of traditional cream for bacterial contamination. Materials and Methods: This is a cross-sectional study. In total, 100 unpasteurized cream samples were collected from 5 regions in Tehran. The Salmonella was enriched in Selenite-F broth, and Yersinia in phosphate buffer in two weeks in cold condition according to CDC, and then were inoculated in MacConky and CIN agar for 24 hours. The suspected colonies were examined for phenotype and their identification was confirmed by API-20 E.  Results:  In general, 29% of tested cream samples were contaminated with at least one kind of bacteria, 3% with Yersinia (1strain Y.enterocolitica, 1 Y.intermedia, 1 frederiksenii), and 2% with Salmonella paratyphi B. The other bacteria like Escheichia coli, Enteobacter, klebsiella, and Citobacter were also isolated. Five samples were contaminated with two kinds of bacteria. Conclusion: The results of this study indicate that more quality control should be applied on the cream produced in the city of Tehran by health control office for food products.